Groundwater Dominates Water Fluxes in a Headwater Catchment During Drought - Kaule, Robin; Gilfedder, Benjamin S. (Frontiers in Water, 2021)
Headwaters make up a large part of the global stream length. They are also especially sensitive to droughts, which affect the stream’s water balance, chemistry, and ecology. Climate change scenarios predict an increasing frequency of extreme weather events. For streams, rivers, and their catchments, this implies a higher probability and frequency of severer droughts and floods. It is likely that during drought, streams depend to a larger extent on groundwater to maintain flow. This study contributes to ongoing research on the effects of drought on headwater catchments and the role of groundwater in the water balance of these systems. Monthly Radon (222Rn) measurements combined with mass balance calculations were used to quantify the spatial and temporal variability of groundwater influx to the Mähringsbach, a headwater catchment in northern Bavaria, Germany. Sampling was conducted in 2019 and 2020, a multi-year drought period, with 2019 being the seventh driest year since the start of records. Thus measurements covered a broad range of flow regimes (0.04 m3 s−1 to ~ 3 m3 s−1 ). 222Rn activities ranged between ~500 Bq m−3 and ~8500 Bq m−3 in the headwater, while further downstream, the activities and variability in activities were lower (~500 Bq m−3 to ~2000 Bq m−3). Results from the 222Rn mass balance showed that in the headwater reaches, the proportion of groundwater varied between 10% and 70 %, while further downstream, it ranged between 0 % and 30 %. There was a clear negative correlation between river discharge and the proportion of groundwater inflow to the stream. Less than 10 % of the total discharge was derived from groundwater during high flow conditions, while under low flow in the headwater reaches, it increased to 70 %. We conclude that aquatic ecosystems in headwaters become increasingly dependent on groundwater during drought periods as a source of water. This dependency will increase in the summer months, given current climate predictions. This knowledge should be used to develop, refine and apply management strategies for streams and the important habitats located in stream sediments (hyporheic zone) under a changing climate.